2018
DOI: 10.3892/ol.2018.8772
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol inhibits the growth of gastric cancer via the Wnt/β-catenin pathway

Abstract: The inhibitory effect of resveratrol on the growth of gastric cancer cells through downregulation of the Wnt/β-catenin signaling pathway were studied. First we determined the effective concentration of resveratrol on the growth and proliferation of MGC-803 gastric cancer cells. Methylthiazolyl tetrazolium assay showed that resveratrol significantly inhibited the proliferation of MGC-803 cells in a dose-dependent manner. Resveratrol induced apoptotic morphological changes in MGC-803 cells. Reverse transcription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…Analyses on a higher number of samples will be necessary to determine if these molecules can function as markers to predict the patients’ outcome. In addition, since EMILIN-2 modulates the Wnt/β-catenin signaling pathway [37] which affects the behavior of gastric cancer cells [59], the loss of EMILIN-2 expression may also display a direct effect of gastric cancer cell growth and progression. Finally, the analyses of EMILIN-1 revealed that in some cases tumor samples were characterized by an altered organization of the molecule in the lamina propria.…”
Section: Discussionmentioning
confidence: 99%
“…Analyses on a higher number of samples will be necessary to determine if these molecules can function as markers to predict the patients’ outcome. In addition, since EMILIN-2 modulates the Wnt/β-catenin signaling pathway [37] which affects the behavior of gastric cancer cells [59], the loss of EMILIN-2 expression may also display a direct effect of gastric cancer cell growth and progression. Finally, the analyses of EMILIN-1 revealed that in some cases tumor samples were characterized by an altered organization of the molecule in the lamina propria.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that RSV can behave differently according to the dose used and the cell type and the metabolic state [120]. Recently, Dai et al [128] showed that RSV inhibits the growth and proliferation of MGC-803 cells of gastric cancer in a dose- and time-dependent way by downregulating the expression of genes related with Wnt pathway as β-catenin, c-myc, and cyclin D1, proteins related with GLUTs gene regulation. On the other hand, Kleszcz, et al [129] did not observe inhibition of c-myc gene expression by resveratrol in FaDu hypopharyngeal carcinoma cells, but the doses used were significantly lower.…”
Section: Inhibition Of Glucose Uptake By Resveratrolmentioning
confidence: 99%
“…(d) Regulating GLUT1 expression through various signaling pathways such as: AMPK [147], Wnt [127,128], Jnk kinases [129,130], sirtuins and histone deacetylases [132].…”
Section: Inhibition Of Glucose Uptake By Resveratrolmentioning
confidence: 99%
“…Resveratrol has been known to be a biologically-active substance that can treat the diseases including obesity, inflammation, diabetes, and cancers [15,16,17,18]. Resveratrol has been shown to effectively inhibit growth in many types of cancer including breast, gastric, lung, and thyroid cancer [19,20,21,22].…”
Section: Anticancer Effects Of Phytochemicals On Thyroid Cancersmentioning
confidence: 99%